Finite-time distributed formation tracking control of multi-UAVs with a time-varying reference trajectory. (18th June 2017) - Zhao, Wei; Li, Renfu; Zhang, Huaipin
Abstract: This article studies finite-time distributed formation tracking control of a second-order multi-unmanned aerial vehicle (UAV) system. To reduce the burden of the system's computation and communication, a distributed framework is designed in the control of the formation configuration, in which a time-varying reference trajectory is known by the following UAVs as exogenous input that decides the UAVs moving target. Then, time-triggered and event-triggered consensus control protocols are proposed and theoretically proved to achieve the formation flight in finite time. Finally, a numerical simulation is conducted for the formation tracking control of a typical multi-UAV system to validate the effectiveness of the proposed control protocols.